Autobiographies of Spanish Refugee Children at the Quaker Home in La Rouvière (France, 1940) : Humanitarian Communication and Children’s Writings - Célia Keren (Les Cahiers de Framespa)
Writing the history of children’experiences in exile entails exploring how children refugees have written about these experiences themselves. It is obviously a challenge to find contemporary texts by refugee children, but even when we do, we are faced with a number of methodological issues. This paper attempts to present and tackle some of those, through the study of fifteen biographical notebooks written around 1940-1941 by Spanish refugee children who lived at La Rouvière in France, in a colony created and run by the American Quakers Friends Service Committee (AFSC). These notebooks form a homogeneous, standardized series, with similar cover and title pages, and a similar structure. They were most certainly composed at the same time, and written as part of the children’s schoolwork in the colony. As much as these children’s experiences, opinions and sentiments, they thus reveal the adult requirements guiding and imposed upon children’s writings. This paper suggests a method for reading such heavily formatted children’s productions as palimpsests, i.e. as the final result of layers of writings applied on top of one another. Each layer constitutes a different narrative about refugee children: the story-writing of humanitarian aid, the Quaker tale of child relief and, finally, the narratives of children’s experiences.